Biodiversity hanging by a thread: the importance of fungal litter-trapping systems in tropical rainforests - Snaddon, Jake L. (The Royal Society, 2012)
The exceptionally high species richness of arthropods in tropical rainforests hinges on the complexity of the forest itself: that is, on features such as the high plant diversity, the layered nature of the canopy and the abundance and the diversity of epiphytes and litter. We here report on one important, but almost completely neglected, piece of this complex jigsaw—the intricate network of rhizomorph-forming fungi that ramify through the vegetation of the lower canopy and intercept falling leaf litter. We show that this litter-trapping network is abundant and intercepts substantial amounts of litter (257.3 kg ha(−1)): this exceeds the amount of material recorded in any other rainforest litter-trapping system. Experimental removal of this fungal network resulted in a dramatic reduction in both the abundance (decreased by 70.2 ± 4.1%) and morphospecies richness (decreased by 57.4 ± 5.1%) of arthropods. Since the lower canopy levels can contain the highest densities of arthropods, the proportion of the rainforest fauna dependent on the fungal networks is likely to be substantial. Fungal litter-trapping systems are therefore a crucial component of habitat complexity, providing a vital resource that contributes significantly to rainforest biodiversity.